Gold‐Catalyzed Highly Diastereoselective Synthesis of Functionalized 3, 4‐Disubstituted Butyrolactams via Phosphatyloxy or Carbonate Double Migrations. Issue 10 (12th July 2013) - Yang, Weibo; Yu, Yang; Zhang, Tuo; Hansmann, Max M.; Pflästerer, Daniel; Hashmi, A. Stephen K.
Abstract A gold‐catalyzed highly diastereoselective synthesis of functionalised 3, 4‐disubstituted butyrolactams via phosphatyloxy or carbonate double migrations is reported, which is proposed to proceed by a tandem 1, 3‐phosphatyloxy or carbonate migration and a "long‐range" 1, 5‐phosphatyloxy or carbonate migration, which overall corresponds to a formal 1, 6‐migration.